Analisis Struktur Dan Gaya Bahasa Dalam Berita Televisi dan Media Sosial Instagram - Sunarni, Sunarni; Sulmayanti, Indah; Sari, Prety Ratna; Firmansyah, Sendy (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to analyze and compare the structure and style of language inpresenting news through two different media, namely television (I-News) andInstagram social media. The background of this study is the shift in people'sinformation consumption patterns from conventional media to digital media,which affects the form of message delivery and the variety of language used.This study uses a qualitative approach with observation, documentation, andcontent analysis techniques on news broadcast on television and Instagramposts by public figures. The results of the analysis show that the structure oftelevision news tends to be systematic, factual, and follows the 5W + 1Hpattern, while the structure of Instagram news is narrative, personal, andreflective. The language style in television news is more formal,straightforward, and informative, while the language style in Instagram poststends to be relaxed, emotive, and communicative. These differences reflect thecharacteristics of the platform, communication goals, and the audiencetargeted by each media. These findings are expected to enrich media linguisticstudies and improve critical literacy in society regarding the variety ofinformation delivery in the digital era.